Atg5-mediated autophagy deficiency in proximal tubules promotes cell cycle G2/M arrest and renal fibrosis. Issue 9 (1st September 2016) - Li, Huiyan; Peng, Xuan; Wang, Yating; Cao, Shirong; Xiong, Liping; Fan, Jinjin; Wang, Yihan; Zhuang, Shougang; Yu, Xueqing; Mao, Haiping
ABSTRACT: Macroautophagy/autophagy protects against cellular stress. Renal sublethal injury-triggered tubular epithelial cell cycle arrest at G2 /M is associated with interstitial fibrosis. However, the role of autophagy in renal fibrosis is elusive. Here, we hypothesized that autophagy activity in tubular epithelial cells is pivotal for inhibition of cell cycle G2 /M arrest and subsequent fibrogenic response. In both renal epithelial cells stimulated by angiotensin II (AGT II) and the murine kidney after unilateral ureteral obstruction (UUO), we observed that occurrence of autophagy preceded increased production of COL1 (collagen, type I). Pharmacological enhancement of autophagy by rapamycin suppressed COL1 accumulation and renal fibrosis. In contrast, genetic ablation of autophagy by proximal tubular epithelial cell-specific deletion of Atg5, with reduction of the LC3-II protein level and degradation of SQSTM1/p62, showed marked cell cycle arrest at the G2 /M phase, robust COL1 deposition, and severe interstitial fibrosis in a UUO model, as compared with wild-type mice. In vitro, AGT II exposure triggered autophagy preferentially in the G1 /S phase, and increased COL1 expression in the G2 /M phase in renal epithelial cells. Stimulation of Atg5 -deficient primary proximal tubular cells with AGT II also resulted in elevated G2 /M arrest and COL1 production. Pharmacological or genetic inhibition of autophagy increased AGT II-mediated G2 /M arrest. Enhanced expression of ATG5, but not the autophagy-deficient ATG5 mutant K130R, rescued the G2 /M arrest, suggesting the regulation of cell cycle progression by ATG5 is autophagy dependent. In conclusion, Atg5 -mediated autophagy in proximal epithelial cells is a critical host-defense mechanism that prevents renal fibrosis by blocking G2 /M arrest.